2010
DOI: 10.1111/j.1365-2036.2010.04492.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the effects of perioperative probiotic treatment on barrier function and post‐operative infectious complications in colorectal cancer surgery – a double‐blind study

Abstract: SUMMARY BackgroundInfection following abdominal operation remains a major factor affecting the morbidity of patients after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
294
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(307 citation statements)
references
References 44 publications
6
294
1
6
Order By: Relevance
“…The conditions for use of prophylactic agents in the colon and rectum may, however, be different. In these organs BT plays a less prominent role and the potential risk of intraoperative contamination appears far greater.In contrast to our results, some recent randomized controlled studies showed a considerable reduction of infectious complications after open radical colorectal surgery with a combined probiotic formula over placebo [15,21,26]. It is not likely that the inconsistent results may attribute to the difference in administered probiotics, because our formula was shown to distinguishingly improve microbial imbalance as well as reduction in organic acids induced by surgery.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The conditions for use of prophylactic agents in the colon and rectum may, however, be different. In these organs BT plays a less prominent role and the potential risk of intraoperative contamination appears far greater.In contrast to our results, some recent randomized controlled studies showed a considerable reduction of infectious complications after open radical colorectal surgery with a combined probiotic formula over placebo [15,21,26]. It is not likely that the inconsistent results may attribute to the difference in administered probiotics, because our formula was shown to distinguishingly improve microbial imbalance as well as reduction in organic acids induced by surgery.…”
contrasting
confidence: 99%
“…Several randomized controlled trials, including pancreatoduodenectomy, hepatobiliary resection and liver transplantation, demonstrate that the use of probiotics in patients undergoing abdominal surgery is a promising approach to the prevention of post-operative infectious complications [8][9][10][11]. Nevertheless, the effectiveness of probiotics treatment for prevention of infectious complications after colorectal surgery remains inconclusive [1,3,[12][13][14][15][16][17][18][19][20][21], possibly due to differences in patient groups, varying preparations of probiotics, and heterogeneity in the quality of methods. Whether or not beneficial bacteria actually survive in the intestine also remains unclear.…”
Section: Descriptionmentioning
confidence: 99%
“…Urinary tract infections, pneumonia, wound infections, intraabdominal abscess and cholangitis are frequently observed among patients undergoing abdominal surgery [9]. Bacterial translocation, the passage of indigenous microorganisms from the intestinal lumen to extra-intestinal sterile sites, plays a significant role particularly for patient undergoing emergency surgery and or who received preoperative total parenteral nutrition (TPN) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mortality and morbidity rates of CRC have been rising in recent years (Raine et al, 2010;Siegel et al, 2012); therefore, CRC represents the third most commonly diagnosed malignant carcinoma and is the fourth most frequent cause of mortality from malignant carcinoma (Liu et al, 2011). The overall incidence of CRC is high at 5% in the general population, whereas the overall 5-year survival rate is less than 60% (Weitz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with CRC are not diagnosed until the disease is at an advanced stage with the presentation of intestinal obstruction or other emergency situations, owing to the absence of early typical symptoms and signs (Liu et al, 2011). Another reason may be that symptoms such as nausea, vomiting, and colicky abdominal pain are common and may be difficult to manage and cause significant physical distress and demoralization (Soriano and Davis, 2011).…”
Section: Introductionmentioning
confidence: 99%